Insurance and Islamic Law - Hasanah, Uswatun (UI Scholars Hub, 2011)
In Islam, insurance has actually been practiced since the time of the Prophet Muhammad saw. The precursor of Islamic insurance, according to some scholars is al-diyah ‘ala al-’aqilah. Al-’aqilah is the habit of Arab tribes having been practiced long before Islam where I f one member of the tribe were killed by other tribe members, the heirs of the victim will be paid with blood money (al-diyah) as compensation by the next of kin of the killer. Next of kin of the killer is known as al-’aqilah. After the arrival of Islam, al-aqilah system was approved by the Prophet PBUH as part of Islamic law. Furthermore, al-’aqilah was contained in the Charter of Medina. In the next period, this al-’aqilah or insurance continued to be practiced by the caliphs, especially during Caliph Umar ibn al-Khattab until now. Islamic Insurance or sharia-based insurance is more nuanced with generosity rather than profit oriented. Therefore, the aspect of mutual help always serves as a primary basis of the practice of Islamic insurance. Islam regards insurance as a social phenomenon formed on the basis of mutual-help and a sense of humanity. Today Islamic insurance is growing rapidly in many countries. This suggests that Islamic insurance is quite attractive to the public in various countries. The problem is, until now there are many people including some Muslims who do not understand Islamic insurance.